2017
DOI: 10.1016/j.econmod.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

How do neighboring peer companies influence SMEs’ financial behavior?

Abstract: Acknowledgments We gratefully acknowledge the contribution of three anonymous reviewers in helping us improve the quality of this paper. Prof. Fernando A. López and Mariluz Maté thanks the financial support offered by the project from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…Differently, lnRES has a significantly negative influence on the peer effect, perhaps because those banks with large reserves already have their own lending strategies. It is worth noting that lnTA and lnDEP do not impact the peer effect in contrast to the findings in some previous studies (e.g., Leary & Roberts, 2014; Maté‐Sánchez‐Val et al, 2017).…”
Section: Empirical Analysiscontrasting
confidence: 99%
“…Differently, lnRES has a significantly negative influence on the peer effect, perhaps because those banks with large reserves already have their own lending strategies. It is worth noting that lnTA and lnDEP do not impact the peer effect in contrast to the findings in some previous studies (e.g., Leary & Roberts, 2014; Maté‐Sánchez‐Val et al, 2017).…”
Section: Empirical Analysiscontrasting
confidence: 99%
“…Likewise, Joo, Yang, and Yang (2016) observe that peer firms cash ratio influences a firm's cash holding decisions among Korean manufacturing firms. Small and medium enterprises (SME) in Spain, show that peers' geographical closeness affects these firms' financial decisions such as profitability, liquidity, and indebtedness (Maté-Sánchez-Val, López-Hernández, & Mur-Lacambra, 2017). Evidence from financial sector also verify the importance of peers in the banking industry in countries outside the U.S. Like, Malik, Mamun, and Amin (2018), find a link between bank's corporate social responsibility (CSR) activities expenses and its peers CSR expenditures in Bangladesh.…”
Section: Literature Review Peer Effects In Financementioning
confidence: 95%
“…In contrast, large-scale companies can gain corporate advantages in activities such as R&D and market development, and some expect that productivity will be high due to the active division of labor within the company (Raspe and van Oort, 2011); it should be noted that this is an area of contention (Huggins and Johnston, 2010). However, since many studies consider the size of a company as a variable that reflects regional economic development (Maté-Sánchez-Val et al, 2017), it was used as a predictor variable in this study. Human capital levels were also considered; Duranton and Puga (2014) reviewed past urban development cases and found that human capital was critical for urban growth.…”
Section: Methods and Datamentioning
confidence: 99%